AriaNN: Low-Interaction Privacy-Preserving Deep Learning via Function Secret Sharing - Ryffel Théo (Sciendo, 2022)
We propose AriaNN, a low-interaction privacy-preserving framework for private neural network training and inference on sensitive data.